Pengaruh Motivasi dan Pengawasan terhadap Kinerja Pegawai CV Putra Niaga Kabupaten Muara Enim - Muhammad Febriansyah; Heriyanto Z. (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This stud y aims to determine whether motivation and The monitoring affects emplo yee performance CV. Putra Niaga, Muara Enim Regency. The sample in this study were 41 respondents who were permanent employees. The sampling method used by the researcher is Random Sampling. This type of research is quantitative research using multiple linear regression analysis techniques which are processed using the SPS S application The results in this stud y are: 1.) M otivation variable has a T count of 3,864 with a significant level of 0.000 < 0.05, this indicates that HO is rejected and Hl is accepted because t count > t table (3,073 > 1,677). This means that motivation has a significant effect on emplo yee performance satisfaction CV. Putra Niaga, Muara Enim Regency. 2.) The monitoring variable has a T count of 2,591 with a significant level of 0.001 < 0.05, this indicates that Ho is rejected and H2 is accepted because t count > t table (2,591 > 1,677). This means that supervision has a significant effect on employee performance satisfaction CV. Putra Niaga, Muara Enim Regency. 3.) that the F value is 8,243 with a significance level of 0.001, because the significance level is 0.05, this regression model can be used for employee performance. This means that f count > f table (8.243>2.79) these results state that motivation, supervision has a direct (simultaneous) effect on the performance of CV employees. Putra Niaga Muara Enim Keywords: M otivation, Supervision, Employee Performance.